2019
DOI: 10.2172/1569033
|View full text |Cite
|
Sign up to set email alerts
|

Safety Analysis of the Mo-99 Production Upgrade to the University of Missouri Research Reactor (MURR) with Highly-Enriched and Low-Enriched Uranium Fuel

Abstract: The University of Missouri (MU) has been working in conjunction with Argonne National Laboratory (ANL) in the National Nuclear Security Administration (NNSA) Material Management and Minimization (M3) Reactor Conversion Program to support conversion of the University of Missouri-Columbia Research Reactor (MURR®) from highly enriched uranium (HEU) to low-enriched uranium (LEU) fuel. MURR is one of five U.S. High Performance Research Reactors (USHPRR) plus a critical facility that plans to convert to the use of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Safety margin evaluations for selected cores in the transition sequence up to and including the equilibrium LEU core are provided in Sections 4 and 5. It was confirmed in previous work that for a prototypic equilibrium LEU core using elements with a mixture of burnup levels and operating at 12 MW, the experimental performance meets or exceeds the performance for a typical HEU core at 10 MW [5,7]. For the LEU core transition cycles, however, experimental performance that will enable MURR to maintain current irradiation services is expected to be a key challenge.…”
Section: Transition Core Planning and Safety Analyses In Support Of Lmentioning
confidence: 61%
See 4 more Smart Citations
“…Safety margin evaluations for selected cores in the transition sequence up to and including the equilibrium LEU core are provided in Sections 4 and 5. It was confirmed in previous work that for a prototypic equilibrium LEU core using elements with a mixture of burnup levels and operating at 12 MW, the experimental performance meets or exceeds the performance for a typical HEU core at 10 MW [5,7]. For the LEU core transition cycles, however, experimental performance that will enable MURR to maintain current irradiation services is expected to be a key challenge.…”
Section: Transition Core Planning and Safety Analyses In Support Of Lmentioning
confidence: 61%
“…Consequently, a power uprate to 12 MW for LEU, along with changes to the reactor limiting safety systems settings (LSSS) for the minimum core coolant flow rate and maximum coolant inlet temperature, was assumed for safety analyses with the preliminary LEU fuel element design [6]. These analyses confirmed that for equilibrium operations with the proposed LEU fuel design, a core power increase, and changes to the MURR Technical Specifications, MURR will maintain sufficient safety margins during steady-state and transient conditions, operating cycle length, and level and spectrum of key neutron fluxes and reaction rates to meet the scientific mission of the facility [5,7,12,13].…”
Section: Approach and Methodology For Analysis Of Transition Coresmentioning
confidence: 90%
See 3 more Smart Citations